تحرير آراء النحاة البصريين والكوفيين في مسألة رافع المبتدأ من خلال كتب الخلاف الثلاثة: للأنباري (577ه)، والعكبري (616ه)، والزبيدي (802ه) = Reviewing the views of Basra and Kufa grammarians on the issue of Rafi’e al-Mubtada’ through the three controversial books of Al-Anbari (577 AH), Al-‘Ukburi (616 AH) and Al-Zubaidi (802 AH) - AlMuqaimi, Majid Hamood Subait; Pa, Mat Taib; Rifa’in@Mohd Rifain, Syakirah; Alosman, Abdulrahman (International Islamic University Malaysia, 2025)
The research aims to review what has been conveyed by the three controversial books, namely: "Al-Insaf fi Masa'il al-Khilaf bayn al-Nahwiyyin al-Basriyyin wa al-Kufiyyin" (Fairness in Issues of Disagreement between the Basra and Kufa ​​Grammarians) by Abu al-Barakat al-Anbari (577 AH), "Kitab al-Tabyeen 'an Mazaahib al-Nahwiyyeen al-Basriyeein wa al-Kufiyyeen" (the Book of At-Tabyeen on the Doctrines of the Basra and Kufa Grammarians( by Abu al-Baqa' al-‘Ukbari (616 AH), and "Kitab I'tilaf al-Nusrah fi Ikhtilaf Nuhat al-Kufah wa al-Basrah") the Book of the Nusra Coalition on the Differences of the Grammarians of Kufa and Basra( by Abu Abdullah al-Sharji al-Zabidi (802 AH), concerning the opinions of the Basra and Kufa grammarians on the issue of Rafi'e al-Mubtada' (the operative factor of nominative case of the subject). The significance of research lies in the fact that these three books are the primary sources that addressed the issues of disagreement between these two schools. Practically, almost every subsequent book, research, or study in the field of discussing the two schools and their points of disagreement refers to these three books, or at least one of them. One of the pivotal issues that significantly influenced the formulation of grammatical rules within both Basra and Kufa grammatical traditions is the concept of al-'Amel (the operative factor). This issue sparked considerable later debate, particularly in attempts to simplify the teaching of grammar, going back to the earlier discussions, specifically on the issue of Rafi’e al-Mubtada’, the three books conveyed the opinions of the Basra and Kufa grammarians, and subsequent books transmitted those opinions without scrutiny. This research followed the inductive approach in tracing what was contained in the three books, and the comparative analysis among them. After examining the views of the Basra and Kufa grammarians on the issue, the following became clear: 1. The Basra grammarians had only two distinct opinions on Rafi'e al-Mubtada’, not four opinions as was reported. 2. The two opinions of the Basra grammarians on the issue are: Rafi'e al-Mubtada’ by inception (al-ibtidāʼ) and Rafi'e al-Mubtada’ by attribution (al-isnād). 3. The concept of inception among Basra grammarians involves two aspects: firstly, the meaning of primacy that demands attention and secondly, making it the first for a second element to be attributed to. 4. Attribution is one of the meanings encompassed within inception. 5. Kufa grammarians have only one opinion on the Rafi'e al-Mubtada’, not two as was previously reported. 6. The view of the Kufa grammarians regarding Rafi'e al-Mubtada’" is more detailed: They said that the subject is Marfoo’ Bi al-Khabar (in the nominative case by the predicate), whether it is singular, derived or rigid, and it is also Marfoo’ bi al-‘Aa’id (in the nominative case by the return) when the predicate is a verbal sentence and the return is not a nominative pronoun. 7. The Basra view that Rafi'e al-Mubtada’ by inception (al-ibtidāʼ) is the preferred opinion, as it aligns more closely with the precise meanings and subtleties conveyed by Arabic sentence structures. 8. Efforts to modernize or simplify Arabic grammar must be based on a deep understanding of the views of the classical grammarians, considering the core meanings and intricate nuances of Arabic sentence structures -features that distinguish the Arabic language- instead of relying on superficial interpretations for the sake of simplification.